2014
DOI: 10.1136/jnnp-2013-306318
|View full text |Cite
|
Sign up to set email alerts
|

Malformation risks of antiepileptic drug monotherapies in pregnancy: updated results from the UK and Ireland Epilepsy and Pregnancy Registers

Abstract: In utero exposure to valproate carries a significantly higher MCM risk than lamotrigine (p=0.0001) and carbamazepine (p=0.0001) monotherapy. In contrast to prior findings, high-dose lamotrigine was associated with fewer MCMs than all doses of valproate. While lamotrigine has a favourable profile compared with valproate for adverse pregnancy outcomes, the requirements for seizure control should not be overlooked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
234
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(252 citation statements)
references
References 13 publications
8
234
0
10
Order By: Relevance
“…10 We found no relationship between occurrence of intrauterine death and AED dose, at least for LTG, CBZ, or VPA, whereas an increased occurrence was identified in women exposed to polytherapy. The observation that AED monotherapy, which is the predominant treatment regimen in pregnant women with epilepsy, [7][8][9] had no apparent impact on the rate of spontaneous abortions or stillbirths is also consistent with a previous report from Rochester based on 788 pregnancies in 256 women with epilepsy. 15 That study found no difference in rates of spontaneous abortions between pregnancies of women with epilepsy on (14.6%) or off (13.6%) AED medication or between pregnancies of women with epilepsy and pregnancies of spouses of men with epilepsy.…”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…10 We found no relationship between occurrence of intrauterine death and AED dose, at least for LTG, CBZ, or VPA, whereas an increased occurrence was identified in women exposed to polytherapy. The observation that AED monotherapy, which is the predominant treatment regimen in pregnant women with epilepsy, [7][8][9] had no apparent impact on the rate of spontaneous abortions or stillbirths is also consistent with a previous report from Rochester based on 788 pregnancies in 256 women with epilepsy. 15 That study found no difference in rates of spontaneous abortions between pregnancies of women with epilepsy on (14.6%) or off (13.6%) AED medication or between pregnancies of women with epilepsy and pregnancies of spouses of men with epilepsy.…”
Section: Methodssupporting
confidence: 77%
“…4,5 Registries set up in the late 1990s have enrolled thousands of pregnancies and enabled comparisons of MCM rates between different AEDs at different dose levels. [6][7][8][9] Other observational studies have revealed differences in postnatal cognitive development.5 For both *These authors contributed equally to this work. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Risks of MCMs were higher with VPA and PB at all doses, and with CBZ at > 400 mg/day. The UK and Ireland Epilepsy and Pregnancy Registers published a subsequent report on an even larger number of pregnancies in each medication group and also demonstrated a significant dose effect with VPA-and CBZ-exposed pregnancies, although the dosedependent trend with LTG was not significant [9]. Additionally, the authors reported that the MCM rate for highdose LTG (>400 mg/day) appeared lower than the MCM rate for pregnancies exposed to < 600 mg/day of VPA, but, again, this was not significant (3.4 % vs 5.0 %; p = 0.31).…”
Section: Dose At Conception Matters For MCM Riskmentioning
confidence: 99%
“…15 These cognitive deficits can occur without MCMs or MAs. For the second-generation AEDs, the risks of MCMs have been reported as 2.0% to 3.7% for lamotrigine, [16][17][18] 0.7% to 2.4% for levetiracetam, 18,19 2.8% for oxcarbazepine, 20 and 4.2% to 4.8% for topiramate.…”
mentioning
confidence: 99%